Pembuatan Hologram Refleksi - Arifah, Arifah; Firdausi, K. Sofjan; Azam, M. (BERKALA FISIKA, 2007)
A Reflection hologram of a white ceramic object has been made on 5000 lines/mm PFG-03M holographic plate. A He-Ne Laser is used to record the holograms. And to reconstruct, it is used white, blue, and yellow light. The holographic plate for making of reflection hologram is PFG-03M. The optimal exposure time lies between 8 and 10 seconds. By reconstruction image white LED, it shows that the image is formed clearer than using blue and yellow light. Â Keywords:Â holography, reflection hologram, reconstruction, exposure time. Â